Population fluctuation of the predacious insects of the pear psylla (Cacopsylla pyri L.) in Attica (Greece) (Bollettino di zoologia agraria e bachicoltura, 2024)
In a pesticide free pear-orchard, in Koropi, Attica (Greece) during theyear 1994-1996 it was found a satisfactory number ofpredacious insects belongingto the farnilies Chrysopidae and Anthocoridae; the most representatives wereChrysoperla carnea Steph. and Anthocoris nemoralis F. The role of C. carneaand A. nemoralis is proven and justifiably so, both are considered to be the mostactive in the control of pear psylla populations ( Cacopsylla pyri L.). Additionallyin the same pear orchard were found many predacious Coccinellidae while theiractivity does not appear to play an important role in the control of the psyllapopulation since their presence in the field is rather incidental. In the field C.carnea appears first in February or March and A. nemoralis follows in March.The population of these insects increases gradually following the populationincreases of their host. The highest density is observed from the end of April tillthe end of July. Reduction of their population follows during the summer monthsto reach again satisfactory levels in the end of September. Especially A. nemoraliswill survive in nature until the end of November and its population will disappearcontemporary with the psylla population.
Keywords: Chrysoperla carnea; Anthocoris nemoralis; pear psylla; Cacopsylla pyri